2018
DOI: 10.21826/2446-8231201873107
|View full text |Cite
|
Sign up to set email alerts
|

Grouping and genetic diversity of different watermelon ecotypes based on agro-morphological traits and ISSR marker

Abstract: ABSTRACT-The genetic diversity of 38 ecotypes of watermelon was evaluated using genetic markers and morphological traits. Analysis of variance showed a signifi cant diff erence for the studied traits. Cluster analysis using UPGMA method based on morphological traits was classifi ed studied ecotypes into four groups. Using 11 primers were obtained 89 polymorphic bands that cluster analysis of molecular data was placed 38 ecotypes into four groups. The genetic diversity structure of the watermelon accessions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Trianthema portulacastrum displayed a moderate level of genetic diversity and Shannon's information index, averaging 0.29 and 0.45, respectively (Table 3). Similar results were observed with SCoT and ISSR markers in Dendrobium nobile (0.28 and 0.43; (Bhattacharyya et al, 2013) and watermelon ecotypes (0.29 and 0.41; (Soghani et al, 2018), both also able to reproduce sexually and clonally. The current study revealed high genetic differentiation levels (GST) and an elevated gene flow: 0.195 and 2.052, respectively.…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 85%
“…Trianthema portulacastrum displayed a moderate level of genetic diversity and Shannon's information index, averaging 0.29 and 0.45, respectively (Table 3). Similar results were observed with SCoT and ISSR markers in Dendrobium nobile (0.28 and 0.43; (Bhattacharyya et al, 2013) and watermelon ecotypes (0.29 and 0.41; (Soghani et al, 2018), both also able to reproduce sexually and clonally. The current study revealed high genetic differentiation levels (GST) and an elevated gene flow: 0.195 and 2.052, respectively.…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 85%
“…Jena and Chand (16) reported that the increased polymorphism between primers used is due to the amplification of genomic regions with high genetic variance between samples. Used 11 ISSR technology primers to find genetic diversity among 38 types of red watermelon, as 89 different bands, the studied species were divided into 4 groups, the study showed that there is no correlation between the results of molecular indicators with phenotypes, and this is due to diversity, high genetics and the influence of environmental factors (32). Elias (13) found that the largest genetic distance between Charleston Gray and Sugar Baby cultivars was 0.349, and the lowest genetic distance between Crimson Sweet and Sugar Baby was 0.149 after using 12 primers belonging to ISSR technology to show genetic diversity among 21 genotypes belonging to three cultivars, from red watermelon they are Crimson Sweet, Sugar Baby and Charleston Gray.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, morphological characteristics have a crucial role in species conservation and plant breeding, it needs to be associated with genetic information to obtain more definitive conclusion. Although several studies have been conducted throughout the world to estimate the morphological diversity of watermelon species (Huh et al 2008;Choudhary et al 2012;Gbotto et al 2016;Singh et al 2017;Soghani et al 2018), experiments on genetic diversity are still limited. Additionally, diseases such as Bacterial fruit blotch (Acidovorax avenae subsp.…”
Section: Introductionmentioning
confidence: 99%